TECHNOLOGICAL PRINCIPLES OF SOCIAL PROJECTING IN THE CIVIL SOCIETY ORGANIZATIONS’ ACTIVITIES IN UKRAINE - Liakh, Viktor; Vainola, Renata; Lekholetova, Maryna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
The ongoing war in Ukraine has exacerbated social vulnerabilities, prompting civil society organizations to adopt innovative strategies. This article explores the use of social projecting as a framework to guide project-based interventions supporting vulnerable populations. The aim is to define the technological foundations of social projecting within the context of Ukrainian civil society organizations, encompassing relevant content, forms, and methods of social work. The study employs methods of analysis, synthesis, and systematization of scientific sources to establish key concepts. Comparative analysis identifies the unique features of social projecting, while legal frameworks are examined to determine the basis for social planning within civil society organizations. Guided by problem-oriented and heuristic approaches, the research analyses and synthesizes existing definitions of "project" and project classification systems. Key findings interpret "projecting" as a process of project creation and implementation, specifically within a social context. Social projecting is defined as a combined theoretical and practical activity aimed at developing projects for social systems, institutions, and objects. These projects rely on social prediction, forecasting, and planning to anticipate and optimize the social impact of interventions. By implementing a robust social projecting framework, civil society organizations in Ukraine can strengthen their project-based interventions, ultimately enhancing the effectiveness of social support initiatives for vulnerable populations during wartime and beyond. In the course of the study, the features of the social projecting process were determined: the contradiction of the social state; multi-vector development of a social object; multiplicity of factors of its being; subjective components of the formation of social expectation and forecast; factors determining various criteria for assessing social status. It is substantiated that the technologies of social projecting are determined by the environment of their implementation, orientation towards a certain group of recipients of social services, types of activities of specialists, features of the social institution. It has been established that four approaches should be taken into account in the development of social projecting technologies: environmental, institutional, person-oriented and activity-based, and their characteristics are provided. The technological foundations of social projecting are defined as a set of content, forms and methods of social work aimed at optimizing social work with different categories of recipients of social services based on social prediction, forecasting and planning of their social qualities and properties. By implementing a robust social projecting framework, Ukrainian CSOs can strengthen their project-based interventions, ultimately enhancing the effectiveness of social support initiatives for vulnerable populations during the current conflict and beyond.